A vade mecum, or, table, containing the substance of such statutes; wherein any one, or more justices of the peace are inabled to act, as well in the sessions, as out of the sessions of peace. With an epitome of Mr. Stamford's pleas of the crown. [electronic resource] :
Summary goes here